2003
DOI: 10.5038/1937-8602.48.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Coptocampylodon pantici n. morpho sp. from the Turonian of NW Serbia

Abstract: This note describes Coptocampylodon pantici, a new morpho species from Upper Cretaceous outcrops of the Poćuta region (NW Serbia). Based on the rudists in superincumbent calcarenites and planktonic foraminifers of the D. concavata Zone overlying the calcarenites, the shallow water "Poćuta limestone" is dated Turonian. The genus Coptocampylodon Elliott is emended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In most cases, there are four, and more seldom, five outer canals. In this respect, our specimens fit well with the illustrated specimens and the description of Ljubović-Obradović and Radoičić (2003). In particular, the specimens with four canals recalling a Maltese cross in transverse sections are the most characteristic (Fig.…”
Section: Stratigraphy Of the Alpine Algal Debris-faciessupporting
confidence: 85%
See 1 more Smart Citation
“…In most cases, there are four, and more seldom, five outer canals. In this respect, our specimens fit well with the illustrated specimens and the description of Ljubović-Obradović and Radoičić (2003). In particular, the specimens with four canals recalling a Maltese cross in transverse sections are the most characteristic (Fig.…”
Section: Stratigraphy Of the Alpine Algal Debris-faciessupporting
confidence: 85%
“…Whether all Coptocampylodon ''species'' in fact belong to laterals of larger dasycladalean alga is, however, questionable. The resemblance between the genus Coprolus and Coptocampylodon lineolatus was interpreted by Ljubović-Obradović and Radoičić (2003) as a case of homeomorphism.…”
Section: Stratigraphy Of the Alpine Algal Debris-faciesmentioning
confidence: 99%
“…(). Other species erected under Coptocampylodon turned out to belong to dasycladacean algae instead of being coprolites, as reflected in the revised diagnosis by Ljubović‐Obradović & Radoičić (), but are excluded from Coptocampylodon and accommodated in Carpathoporella or elsewhere (Schlagintweit et al . ; Schlagintweit & Gawlick ).…”
Section: Systematic Ichnologymentioning
confidence: 99%
“…The isolated, slightly curved specimens (with rounded ends) exhibiting longitudinal ribs are comparable large, attaining diameters of up to 1 mm and lengths of up to 3 mm, whereas the transverse sections in the thin-section material only attain diameters of up to 0.5 mm. As one discriminating feature of "species" established later on, the number of the marginal-longitudinal grooves became important (e.g., Patrulius 1966;Dragastan 1989;Schlagintweit et al 2002;LjuboviT-ObradoviT and RadoibiT 2003). Elliott (p. 298) concluded that Coptocampylodon "comprises the skeletal remains of a small octocoral in which horny and calcareous joints alternated".…”
Section: Coptocampylodon-carpathoporella: a Historical Reviewmentioning
confidence: 99%
“…Besides the interpretation as octocoral sclerites by Elliott (1963), a view not followed by subsequent workers, Coptocampylodon was-as already mentioned-interpreted as algal remains and the isolated specimens as crustacean coprolites (Cuvillier et al 1969). The latter opinion was regarded as a simple case of homeomorphism by LjuboviT-ObradoviT and RadoibiT (2003). Livkovic and Bogner (2006) studied isolated specimens of Coptocampylodon lineolatus from the Eocene of Croatia demonstrating that these show similar chemical composition as the host marl.…”
Section: Coptocampylodon-carpathoporella: a Historical Reviewmentioning
confidence: 99%